On Immunologists and Microbiologists: Ground Zero in the Battle for Interdisciplinary Knowledge - Christine A. Biron (American Society for Microbiology, 2010)
ABSTRACT The individual disciplines of microbiology and immunology are exploding with new information necessary for understanding host-pathogen relationships, infectious diseases, cancer, and autoimmunity. Because of overlapping scientific interests, immunologists and microbiologists often share common academic affiliations. The coexistence is uneasy. Significant problems arise because the groups have evolved different intellectual traditions. Pressures are intensified by sporadic changes in perceptions of their relative worth. As the mixing of microbiologists and immunologists can be likened to ground zero in the fight for interdisciplinary knowledge, it is useful, at this time of escalating data acquisition and growing appreciation for multidisciplinary research, to examine their histories, the challenges to amalgamation, and the advantages of their association for the advancement of knowledge and the delivery of protection against disease. The exploration supports a recommitment to integration of the disciplines and a proposal to facilitate this by inclusion of expertise bridging the areas.